Provide a Framework for the Application of Open Policy Making in Parliament of Iran - Mohsen Eynali; Seyed Abbas Ebrahimi; Mohsen Farhadinejad; Hasan Danaeefard (مدیریت دولتی)
ObjectiveOpen policy making represents an innovative and modern approach for governments to create and deliver policies that are effectively aligned with the rapid changes and evolving demands of a fast-paced, digital world. This approach is emerging as a vital and progressive methodology in the field of government administration, particularly in the era of information technology and global connectivity. The anticipated outcomes of adopting open policy making are manifold. They include achieving more optimal policy adoption through collaborative efforts, garnering robust stakeholder support for the implementation of desired policies, enhancing access to critical data for both elites and the general public, significantly increasing public participation in the policy-making process, and substantially boosting public trust in governing institutions, such as the Shura Council. Within this framework, the current research is specifically focused on developing a comprehensive open policy framework tailored for the Parliament of Iran, aiming to modernize and improve its policy-making processesMethodsThis research is grounded in the interpretative paradigm of the philosophical foundations of research and is applied in nature. It utilizes a mixed-methods approach for data collection. The target population encompasses all scientific experts in public policy (including faculty members of universities and research institutions with expertise in decision-making and public policy) and executive experts (including current and former members of the Parliament). Data collection tools included semi-structured interviews, library research, and literature review for the qualitative part, and questionnaires for the quantitative part. Using snowball sampling, 22 exploratory and in-depth interviews were conducted with scientific and executive public policy experts. In the quantitative phase, 44 individuals were selected through stratified probability sampling. Grounded theory and Maxqda10 software were used for data analysis in the qualitative part, while the structural equation modeling approach was applied in the quantitative part.ResultsData analysis identified the general dimensions and preconditions of the open policy model, along with the components and elements constituting its main dimensions, including understanding the problem, developing solutions, compiling, and evaluating. Quantitative findings demonstrate the positive and significant effect of transparency, a key dimension of open policy, on problem understanding, solution development, formulation, and evaluation. Similarly, public participation significantly impacts problem understanding, solution development, formulation, and evaluation. The results also highlight the direct and meaningful impact of cooperation, another general dimension of open policy, on these aspects. Furthermore, the analysis revealed that understanding the problem positively and significantly affects solution development, which in turn influences formulation and evaluation.ConclusionGiven the fundamental principles of transparency, participation, and cooperation, the implementation of the open policy model is essential and highly beneficial for strengthening the overall performance of the Parliament. By embracing this model, the Parliament can significantly enhance its efficiency and effectiveness in fulfilling its legal roles, while also fostering a more inclusive and collaborative approach in its governance. This adoption not only aids in decision-making processes but also ensures greater accountability and public engagement.